Definitive obturator rehabilitation on the maxilla defect post-tumor surgery - Abd. Karim (Indonesian Journal of Prosthodontic, 2022)
Background: Obturator is a prosthesis to replace tissue lost post tumor surgery in the maxilla called maxillectomy. Obturator is made of acrylic and consists of surgery, intermediate, and definitive obturator. Definitive obturator is made using Hollow bulb technique to be light and stable when used. In this case, a definitive obturator was made for a patient using intermediate obturator. Objectives: To inform that obturator can rehabilitate maxillary defect to restore the patient’s mastication, digestive, phonetic, aesthetic and psyche functions. Case report: A 28-year-old man came for postoperative cleft management. Diagnosis is Post OP Hemi maxillectomy Dextra. The procedure begins with impression to obtain study model and the making of individual tray. The next visit is grinding the remaining teeth for occlusal rest placement. Double impression is done to obtain working model and making the bite block. The third visit is bite block try-in on the patient and placed to working model for fixation on the articulator, followed by tooth color determination and laboratory instructions. The fourth visit is wax obturator try-in and checking occlusion, articulation, aesthetics and phonetics. The fifth visit is definitive obturator insertion and follow up. Conclusion: Definitive obturator can rehabilitate defects post maxillary tumor surgery.Keywords: Maxillary defect, definitive obturator, Hollow bulb technique